Status Hukum Rumah Berdasarkan Perjanjian Pengikatan Jual Beli Ketika Developer Pailit - Felicia Vanesa Japri; Richard C. Adam (LPPM Universitas Ekasakti Padang, 2023)
The demand for housing creates business opportunities for private individuals to venture into the residential property sector. Housing development companies, also referred to as developers, can face bankruptcy. When declared bankrupt, the developer often maintains a legal relationship with the homebuyer, based on the Sale and Purchase Agreement. This research aims to determine the legal status of a house in situations where the developer goes bankrupt, in accordance with Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. This study employs a qualitative research method with a normative approach, focusing on statutory aspects. The research findings indicate that, as per the Bankruptcy Law, the Sale and Purchase Agreement between the developer and the homebuyer is voided. This occurs because ownership rights to both the land and house remain with the developer, making them assets subject to bankruptcy proceedings. Consequently, the homebuyer may apply as a creditor simultaneously, seeking compensation.